Bizet Carmen : ópera para orquesta - Kostelanetz, Andre; Kopstelanetz, Andre (San José, Costa Rica : CBS-INDICA)
Sumario: Música de ópera francesa "Carmen"
Keywords: OPERA FRANCESA; GRABACIONES SONORAS